A review of current progress of recycling technologies for metals from waste electrical and electronic equipment. (20th July 2016) - Zhang, Lingen; Xu, Zhenming
Abstract: The development of the recycling technologies for waste electrical and electronic equipment (WEEE) has entered a new stage. The WEEE disposing technologies have evolved from simple disassembly, classification and sorting to high value-added utilization technologies. In the past decade, some modified and novel technologies have been developed to recover metals from WEEE. This paper focuses on the recycling of metals from WEEE. The recycling principle, separating process, and optimized operating parameters of existing technologies are summarized and discussed in detail. Based on traditional recycling technologies of WEEE, pyrometallurgical technology and some mild extracting reagent, such as chloride medium, ammonia–ammonium and non-cyanide lixiviants can effectively recycle metals. Compared with the conventional acid and cyanide leaching, they have vast improvements in aspect of environmental protection. More than 98% of Cu and 70% of Au can be extracted. In addition, electrochemical technology, supercritical technology, vacuum metallurgical technology, etc. are also applied to recycle WEEE. The recovery rate of Cu and Pb under optimum conditions is around 84.2% and 89.4% respectively in supercritical water oxidation (SCWO) combined with electrokinetic (EK) technology. Vacuum technology has good environmental performance due to its avoiding discharge of waste water. Other new technologies such as ultrasound technology, mechanochemical technology, and molten salt oxidation technology have also been tried to recycle metals from WEEE. Regrettably, although many endeavors to develop recycling technologies have been attempted, these technologies are still relatively single and limited because WEEE is a complex system. Hence, the shortages and defects of each technology are discussed from the perspective of technological promotion and environmental protection. Furthermore, the outlook about the further development of recycling technologies for metals from WEEE is presented. Graphical abstract: Highlights: Current recovery technologies for metals in WEEE are summarized and reviewed. Defects and shortages of existing technologies are analyzed in detail. Suggestions for technology promotion and environmental protection are presented.